Characterisation of acylated anthocyanins from red cabbage, purple sweet potato, and Tradescantia pallida leaves as natural food colourants by HPLC-DAD-ESI(+)-QTOF-MS/MS and ESI(+)-MSn analysis. (1st August 2023) - Steingass, Christof B.; Burkhardt, Jonas; Bäumer, Vicky; Kumar, Keshav; Mibus-Schoppe, Heiko; Zinkernagel, Jana; Esquivel, Patricia; Jiménez, Víctor M.; Schweiggert, Ralf
Graphical abstract: Highlights: Detailed analysis of acylated anthocyanins in red cabbage and sweet potato leaves. Tradescantia pallida leaves contain uncommon tetraacylated anthocyanins. Superior stability of acylated anthocyanins during heating of a test beverage. Acylated anthocyanins exert brilliant colours over a broad pH range. Uncommon vis spectra of Tradescantia anthocyanins are reported. Abstract: Anthocyanins in red cabbage, sweet potato, and Tradescantia pallida leaves were characterised. A total of 18 non–, mono-, and diacylated cyanidins was identified in red cabbage by high performance liquid chromatography-diode array detection coupled to high-resolution and multi-stage mass spectrometry. Sweet potato leaves contained 16 different cyanidin- and peonidin glycosides being predominantly mono- and diacylated. In T. pallida leaves, the tetra-acylated anthocyanin tradescantin prevailed. The large proportion of acylated anthocyanins resulted in a superior thermal stability during heating of aqueous model solutions (pH 3.0) coloured with red cabbage and purple sweet potato extracts as compared to that of a commercial Hibiscus -based food dye. However, their stability was still outperformed by that of the most stable Tradescantia extract. Comparing vis spectra from pH 1–10, the latter had an additional, uncommon absorption maximum at approx. 585 nm at slightly acidic to neutral pH values, yielding intensely red to purple colours.